Changes in Mycobacterium tuberculosis genotype families over 20 years in a population-based study in Northern Malawi. - Judith R Glynn; Saad Alghamdi; Kim Mallard; Ruth McNerney; Richard Ndlovu; Lumbani Munthali; Rein M Houben; Paul E M Fine; Neil French; Amelia C Crampin (PLoS ONE)
Background Despite increasing interest in possible differences in virulence and transmissibility between different genotypes of M. tuberculosis, very little is known about how genotypes within a population change over decades, or about relationships to HIV infection. Methods and principal findings In a population-based study in rural Malawi we have examined smears and cultures from tuberculosis patients over a 20-year period using spoligotyping. Isolates were grouped into spoligotype families and lineages following previously published criteria. Time trends, HIV status, drug resistance and outcome were examined by spoligotype family and lineage. In addition, transmissibility was examined among pairs of cases with known epidemiological contact by assessing the proportion of transmissions confirmed for each lineage, on the basis of IS6110 RFLP similarity of the M tuberculosis strains. 760 spoligotypes were obtained from smears from 518 patients from 1986-2002, and 377 spoligotypes from cultures from 347 patients from 2005-2008. There was good consistency in patients with multiple specimens. Among 781 patients with first episode tuberculosis, the majority (76%) had Lineage 4 ("European/American") strains; 9% had Lineage 3 ("East-African/Indian"); 8% Lineage 1 ("Indo-Oceanic"); and 2% Lineage 2 ("East-Asian"); others unclassifiable. Over time the proportion of Lineage 4 decreased from >90% to 60%, with an increase in the other 3 lineages (p<0.001). Lineage 1 strains were more common in those with HIV infection, even after adjusting for age, sex and year. There were no associations with drug resistance or outcome, and no differences by lineage in the proportion of pairs in which transmission was confirmed. Conclusions This is the first study to describe long term trends in the four M. tuberculosis lineages in a population. Lineage 4 has probably been longstanding in this population, with relatively recent introductions and spread of Lineages1-3, perhaps influenced by the HIV epidemic.